An assessment of the accuracy and utility of the primary care electronic medical record as used by the British Army. Issue 5 (25th November 2015) - Cox, Andrew T; Gillingham, S; Johnson, S A; Sharma, S; Wilson, D
Abstract : Introduction: For the purposes of patient safety, audit and research, the electronic patient record (EPR) must be accurate and searchable. No evaluation of the accuracy of EPRs compared with paper records has been made. Furthermore, the use of Read codes is known to be heterogeneous. This study was designed to evaluate the EPR used by the UK Armed Forces. Methods: A cross-sectional study reviewing the paper records and EPRs of 50 consecutive soldiers posted to a British Army Training Regiment. Results: There was a pre-enlistment summary in only 38% of the paper notes, although 24% had some primary care records from prior to enlistment. There were 357 entries that should have been transferred to the EPR. Of these, only 190 (53.2%) were transferred with appropriate Read codes, while only 24% of patients reviewed had all their entries appropriately Read coded. There were 168 secondary care letters discovered with 122 (72.6%) generically Read coded and 46 (27.4%) using an appropriate Read code. Of those letters with more than one potential Read code, 34 (73.9%) were coded using all appropriate Read codes. Several incidental errors in the medical records were also discovered with significant patient safety implications. Conclusions: The historical paper-based medical record was found to have many data missing. The transfer of these paper records to the EPR has been inaccurate with many records not transferred or transferred ineffectively. These findings have an impact on patient safety, audit and data security and should trigger a review of how the Armed Forces manage their primary care records.